Adaptive overcurrent protection considering critical clearing time for a microgrid system - Tummasit N. (2017)
© 2015 IEEE. This paper presents research on adaptive overcurrent protection by considering critical clearing time (CCT) for a microgrid system (MGS). The studied case is located in Mae-Sariang district, Chiang Mai province which is a remote area. It is composed of many kinds of user loads, an energy storage system and distributed generations (DGs). When faults occur while MGS is performing in the grid-connected mode or island mode, very different fault current level (FCL) values occur. According to this event, the overcurrent relay might malfunction and the generators might become unstable. The FCL change depends on the grids while the system is in the grid-connected mode. On the other hand, the FCL depends on DGs while the system is in the island mode or stand-alone mode. Our research was carried out in the 22kV distribution system of the Provincial Electricity Authority of Thailand (PEA). System analysis used the DigSILENT Power Factory software and the Real Time Digital Simulation (RTDS). Test results show the fault current, CCT and overcurrent relay setting.